Seminal plasma proteins and sperm quality of Romosinuano and Costeño con Cuernos bulls - Fernández N., Juan Carlos (2022)
The aim of this study was to determine by SDS PAGE the protein profile of the seminal plasma of Romosinuano (ROMO) and Costeño con Cuernos (CCC) bulls and their relationship with sperm quality parameters in fresh and thawed semen. Three ejaculates per bull were collected by electro-ejaculate from 10 ROMO and 10 CCC sires. Viability (VF), mass motility (MMF), individual rapid progressive motility (MIRPF) and sperm concentration (CE) were determined in fresh semen. Seminal plasma (PS) was obtained by double centrifugation. Individual motility of rapid progressives (MIRPPC), progressivity (PRPC), rapid progressives (RPPC) and medium progressive (MPPC) were determined in thawed semen, in both cases using the CASA computerized analysis system. Additionally, viability (VPC) and membrane integrity were determined by the hypoosmotic test. Proteins were separated by polyacrylamide gel electrophoresis (SDS PAGE). The data was analyzed by Student’s T test and the presence of proteins by Chi square. The relationship between proteins and seminal quality parameters using Pearson’s correlation test and principal components of forward regression. In fresh semen, differences (p<0.05) were found between the two breeds for CE and MIRPF, and in thawed semen for VPC. Ten protein bands were evidenced in ROMO bulls and 7 in CCC bulls. The 13, 83 and 121 kDa bands were positively related and the 15 kDa negatively with VF from ROMO bulls. Protein bands 21, 25, 102 and 174 were associated with both MF and CE in ROMO bulls. In conclusion, the electrophoretic profiles of seminal plasma proteins from Romosinuano and Costeño con Cuernos bulls were established. The relationships between the bands detected with the sperm quality could partly explain the fertilizing capacity of the sperm of these breeds.